A Compact Wideband Printed Antenna for 4G/5G/WLAN Wireless Applications. (10th September 2019) - Yang, Ming; Sun, Yufa; Li, Fan
Abstract : A compact wideband printed antenna with deca-band 4G/5G/WLAN for mobile phone devices is proposed in this paper. The complete structure is composed of a monopole antenna and a coupling strip, occupying a small C-shape PCB area of 27 × 10.8 mm 2 . This antenna, which is printed on FR4 substrate with 0.8 mm thickness and fed by a coaxial cable, can provide three wide operating bandwidths that cover 685–1012 MHz, 1596–2837 MHz, and 3288–3613 MHz for 4G/5G/WLAN communication systems. The gains and total radiation efficiencies of the antenna in the low, middle, and high bands are 1.4 dBi–2.5 dBi and 38%–47%, respectively. Besides, the measured results are in good agreement with the simulated results. Further experiments demonstrate that the proposed antenna exhibits a good performance for mobile phones.